2022
DOI: 10.7554/elife.74708
|View full text |Cite
|
Sign up to set email alerts
|

Distance estimation from monocular cues in an ethological visuomotor task

Abstract: In natural contexts, sensory processing and motor output are closely coupled, which is reflected in the fact that many brain areas contain both sensory and movement signals. However, standard reductionist paradigms decouple sensory decisions from their natural motor consequences, and head-fixation prevents the natural sensory consequences of self-motion. In particular, movement through the environment provides a number of depth cues beyond stereo vision that are poorly understood. To study the integration of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…While we investigated vLGN’s function mostly in situations where visual and behavioral signals were intentionally separated, during natural behavior movement-induced reafferent and exafferent signals are strongly and necessarily intermixed, as during saccades. These signals need to be discriminated, e.g., to estimate distance using monocular cues ( 44 , 45 ). Accordingly, using the visual cliff paradigm, we were able to show that vLGN-deficient mice have severe impairments in depth perception (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we investigated vLGN’s function mostly in situations where visual and behavioral signals were intentionally separated, during natural behavior movement-induced reafferent and exafferent signals are strongly and necessarily intermixed, as during saccades. These signals need to be discriminated, e.g., to estimate distance using monocular cues ( 44 , 45 ). Accordingly, using the visual cliff paradigm, we were able to show that vLGN-deficient mice have severe impairments in depth perception (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that mice can use monocular and binocular cues to estimate depth ( 44 ) and that monocular perception requires motion for proper depth estimation ( 45 ). Therefore, we decided to test depth perception using a classical visual cliff paradigm (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The role of eye and head movements in visual perception has been well‐studied in a number of taxa (see reviews: Kral, 2003 ; Land, 1999 ). For example, mice will alter their head position and head movements when completing a jumping task under monocular conditions, potentially to facilitate distance estimation via position or motion parallax (Parker et al., 2022 ). As such, sensory and motor systems can be thought of in a loop framework, each system acting as an input for the other.…”
Section: Introductionmentioning
confidence: 99%
“…Active sensing strategies are the processes by which sensory flow is modified by movement (Hofmann, Sanguinetti‐Scheck, Künzel, et al., 2013 ; Parker et al., 2022 ). Movements can be isolated to the sensor/emitter of the signal, or be more wide ranging, consisting of whole‐body movements (Hofmann, Sanguinetti‐Scheck, Künzel, et al., 2013 ; Kral, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation